THE EFFECTIVENESS OF USING COMIC STRIPS TOWARDS STUDENTS' SKILL IN WRITING RECOUNT TEXT FOR THE TENTH GRADERS AT MA ASSA'IDIYAH TANGGULREJO - Meylita Eka; Mazidah, Eva Nur (ETNOLINGUAL, 2024)
This research proves the effectiveness of comic strips as a learning media on students' writing skills at MA Assa'idiyah Tanggulrejo in recount texts. This research aims to help students in preparing text structures using simple past tense through comic strips. This research was use pre-experimental design with quantitative method and divided into three parts, there are pre-test, treatment, and post-test. The data collected was in the form of a writing test (pre and post-test) on 40 tenth grade students at MA Assa'idiyah Tanggulrejo. Data analysis was carried out from the SPSS calculation application using the t-test formula. The results of data analysis shown that the mean of post-tests increased by 1.80 from the mean of pre-tests. The value in the t-test formula was 12.502, while the t-table at the 0.05 significance level and the degree of freedom (df) = 39 was 2.023. It able to assume that the Null Hypothesis (Ho) has been rejected and the Alternative Hypothesis (Ha) has been accepted because the t-test value (12.502 > 2.023) is higher than the t-table. In other word, that there is a significant impact on the use of comic strips as a media to enhance students' writing abilities, especially in recount text.